ON BEING OF TWO MINDS: THE STRUCTURE OF SCIENTIFIC EVOLUTION - Brown, Peter J. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1982)
Astonishing strides have been taken in the last few years in detecting the physical workings of the human brain, and these have inevitably affected the prospects of our understanding human behaviour and educating it. In an essay that playfully draws an analogy between the behaviour of neurons and the behaviour of people, Brown draws a moral or two about the manner in which groups of people should pursue science, especially in a period when a time-honoured paradigm may be reaching the end of its usefulness. The implication he draws from what we know of the complementarity of the brain’s two halves points towards the restoration of a balance in education - a balance long distorted by a bias towards logic at the expense of intuition if we are to use our brains efficiently in the way they were designed. RÉSUMÉ Des progrès étonnants ont été réalisés ces dernières années pour détecter les travaux physiques du cerveau humain, ce qui a inévitablement multiplié nos chances de mieux comprendre le comportement humain et de l’éduquer. Dans cet essai où il dresse en badinant l’analogie entre le comportement des neurones et celui des hommes, Brown tire une ou deux leçons sur la façon dont les gens devraient poursuivre des recherches scientifiques, surtout à une époque où l’utilité d’un paradigme qui jouit des honneurs du temps commence peut-être à tirer à sa fin. Les conclusions que tire Brown sur ce que nous savons de la complémentarité des deux hémisphères du cerveau indiduent le rétablissement d’un certain équilibre en éducation (equilibre chancelant du fait qu’on a trop longtemps insisté sur la logique aux dépens de l’intuition), pourvu que nous nous servions de notre cerveau à bon escient.